The efficacy of expanded non‐invasive prenatal testing (NIPT) in a high‐risk twin pregnancies cohort - Meng Meng; Jianping Chen; Yingjun Yang; Yun Zhang; Gang Zou; Fenhe Zhou; Xing Wei; Yuchun Ge; Jia Zhou; Luming Sun (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Our objective was to evaluate the efficacy of expanded non‐invasive prenatal testing (NIPT) that includes both trisomies and copy number variants (CNVs) in high‐risk twin pregnancies. Material and Methods A prospective, double‐blinded cohort study was conducted, enrolling 73 high‐risk twin pregnancies characterized by increased risk of genetic disorders due to factors such as increased nuchal translucency, structural anomalies, fetal growth restriction, and other factors associated with chromosomal abnormality. Participants underwent invasive karyotyping and chromosomal microarray analysis, alongside separate expanded NIPT for research purposes. The sensitivity, specificity, positive predictive value, and negative predictive value of expanded NIPT were calculated. Results The cohort included 24 monochorionic and 49 dichorionic twin pregnancies. The median cell‐free fetal DNA concentration in expanded NIPT was 16.7% (range 3.86%–49.1%), with a test failure rate of 1.4% (1/73). High‐risk findings for trisomy 21/13/18 were identified in five cases (6.8%), Turner syndrome in one case (1.4%), and CNVs indicative of high risk for clinically significant microdeletion/microduplication syndromes (MMS) in ten cases (13.7%). Of these, 56 cases (76.7%) tested NIPT negative, revealing one false‐negative for 45, X and five false‐negatives for CNVs. Expanded NIPT achieved a detection rate of 100% (5/5) for trisomy 21/13/18 with a false‐positive rate of 0% (0/5), a detection rate of 33.3% (1/3) for sex chromosome abnormalities with a false‐positive rate of 0% (0/3), and a detection rate of 66.7% (4/6) for MMS with a false‐positive rate of 3.0% (2/67). The positive predictive values for trisomy T21/13/18, sex chromosome abnormalities, and known MMS were 100% (5/5), 100% (1/1), and 66.7% (4/6) in the expanded NIPT, respectively. Conclusions The expanded NIPT demonstrated high detection rates for common trisomies and moderate detection rates for prenatal MMS in high‐risk twin pregnancies. Further studies with large sample sizes in low‐risk populations are needed.